2011
DOI: 10.2136/vzj2010.0139
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Terrestrial Environmental Observatories in Germany

Abstract: Multicompartment and multiscale long‐term observation and research are important prerequisites to tackling the scientific challenges resulting from climate and global change. Long‐term monitoring programs are cost intensive and require high analytical standards, however, and the gain of knowledge often requires longer observation times. Nevertheless, several environmental research networks have been established in recent years, focusing on the impact of climate and land use change on terrestrial ecosystems. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
304
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 450 publications
(306 citation statements)
references
References 50 publications
1
304
0
1
Order By: Relevance
“…The CZEN has helped build an active international community of scientists, many of whom participate in the annual American Geophysical Union (AGU) meetings. A handful of nations or collections of nations have funded CZO networks, including the USA (Brantley et al, 2017b), France (Gaillardet et al, 2018), Germany (Zacharias et al, 2011), the European Union (Banwart et al, 2017), and China (Tahir et al, 2016).…”
Section: Czen and Czosmentioning
confidence: 99%
“…The CZEN has helped build an active international community of scientists, many of whom participate in the annual American Geophysical Union (AGU) meetings. A handful of nations or collections of nations have funded CZO networks, including the USA (Brantley et al, 2017b), France (Gaillardet et al, 2018), Germany (Zacharias et al, 2011), the European Union (Banwart et al, 2017), and China (Tahir et al, 2016).…”
Section: Czen and Czosmentioning
confidence: 99%
“…Rollesbroich is part of the TERENO network (Zacharias et al, 2011). Information and additional data were collected showing that land surface properties are spatially heterogeneous distributed at the Rollesbroich site: (1) single fields at the Rollesbroich site are managed by different farmers; information the land owners provided, as well as periodic camera shots and grass height measurements around the EC towers indicated that the timing of fertilization and grass cutting as well as the amount of manure applied varied between the single fields during the measurement period; (2) soil type distribution as displayed in the German soil map shows heterogeneity (Arbeitsgruppe BK50, 2001); (3) (4) during the eddy covariance measurement period, soil moisture and soil temperature data were collected in 10 min.…”
Section: Test Sites and Ec Tower Setupmentioning
confidence: 99%
“…Beyond the new mesoscale observations, extensive catchment databases now exist to support hypothesis testing including the TERENO (Zacharias et al, 2011), MOPEX (Duan et al, 2006), contiguous USA benchmarking (Newman et al, 2015a), GRDC (http://www.bafg.de/GRDC/ EN/01_GRDC/13_dtbse/database_node.html), and EURO-FRIEND databases (Stahl et al, 2010). Recent similarity studies have systematically analyzed large numbers of catchments focusing on streamfloworiented signatures such as the runoff coefficient, baseflow index, and slope of the flow duration curve and have then explored relationships between these signatures and model process timescales .…”
Section: Data Requirementsmentioning
confidence: 99%